The effect of horizontal mergers on efficiency and market power: An application to the Argentine hamburger market - Germán Coloma (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2019)
This paper analyzes the behavior of the Argentine hamburger market during the period 2013-2018, to see if an important merger that occurred by the end of 2015 (the BRF/MRP merger) had any discernable market-power or efficiency effects. To do this, we run an econometric demand-and-supply model, and we find that there is an appreciable cost reduction that more than counterbalances the price increases induced by the merger. This implies that total consumers' surplus may have grown as a consequence of the merger.
Keywords: C32; L13; L41; L66; 330; Merger; hamburger; Argentina; market power; efficiency